2022
DOI: 10.36909/jer.16963
|View full text |Cite
|
Sign up to set email alerts
|

Assertion-Evidence versus Traditional PowerPoint: An Investigation of the Impact of Slide Structure on Engineering Students’ Cognitive load, Motivation, and Performance

Abstract: Engineers are typically asked to create slides to present their technical presentations in conferences, classrooms, and meetings. Most slides used by engineers follow a traditional PowerPoint style of a topic-subtopic structure. Contrary to the traditional bulleted PowerPoint, the Assertion Evidence (AE) slide structure replaces default phrase headlines with a succinct sentence, containing the main idea of the slide. While prior research has demonstrated that the AE style of presentations is effective towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…First, PPTs are lauded for their capacity to boost comprehension through a combination of text and visual assistance, so making complicated concepts more digestible (Hidayanti & Widya, 2018). This multimedia approach aligns with research that suggests individuals tend to learn more effectively when words and pictures are presented simultaneously (Alzayed & Alzamel, 2022). Moreover, they make the learning process more practical, which benefits both teachers and students by speeding instruction and concretizing abstract concepts.…”
Section: The Analysis Of the Reflection Digital Multimodal Instructio...supporting
confidence: 66%
“…First, PPTs are lauded for their capacity to boost comprehension through a combination of text and visual assistance, so making complicated concepts more digestible (Hidayanti & Widya, 2018). This multimedia approach aligns with research that suggests individuals tend to learn more effectively when words and pictures are presented simultaneously (Alzayed & Alzamel, 2022). Moreover, they make the learning process more practical, which benefits both teachers and students by speeding instruction and concretizing abstract concepts.…”
Section: The Analysis Of the Reflection Digital Multimodal Instructio...supporting
confidence: 66%
“…Numerous previous studies have explored the impact of Assertion-Evidence design on students' retention of English grammatical knowledge. For instance, Alzayed and Alzamel (2022) conducted research that demonstrated significantly higher test scores among students who were taught English grammar using Assertion-Evidence Design compared to a control group that followed traditional teaching methods. Similarly, Garner and Alley (2016) found that students instructed with Assertion-Evidence Design exhibited greater retention of grammatical concepts compared to those taught using traditional approaches.…”
Section: Research Gap and The Need For The Present Studymentioning
confidence: 99%
“…The Assertion-Evidence Design (AED) is an instructional approach that involves presenting a clear and concise claim (assertion) supported by relevant evidence, such as examples, data, and research findings. This teaching method is grounded in cognitive theory, which posits that information is better retained when presented in a structured and logical manner (Alzayed & Alzamel, 2022). Cognitive theory focuses on the internal processes involved in memory and knowledge acquisition, and it originated in the 1930s with Jean Piaget's observations of psychological reactions within the behaviorist school (Alzayed & Alzamel, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation